2015
DOI: 10.1016/j.susc.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Ion scattering spectroscopy intensities for supported nanoparticles: The hemispherical cap model

Abstract: Nanoparticles of one element or compound dispersed across the surface of another substance form the basis for many materials of great technological importance, like catalysts, fuel cells, sensors and biomaterials. Nanoparticles also often grow during thin film deposition. The size and number density of such nanoparticles are important, often estimated with electron or scanning tunneling microscopies. However, these are slow and often unavailable with sufficient resolution for particles near 1 nm. Because the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(75 citation statements)
references
References 14 publications
0
75
0
Order By: Relevance
“…The normalized Ag and Ti LEIS signals directly measure the fraction of the surface area that is covered by the Ag particles including a shadowing effect. 73 The evolution of the normalized Ag and Ti LEIS signals is plotted versus Ag coverage in Figure 3 and compared with two typical growth models. The Ag coverages reported in this paper are given in monolayer (ML), where 1 ML is defined as 7.36 × 10 18 atoms/m 2 , which is the areal number density of coordinatively unsaturated O atoms on the ideal bulk-terminated TiO 2 (100) surface.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The normalized Ag and Ti LEIS signals directly measure the fraction of the surface area that is covered by the Ag particles including a shadowing effect. 73 The evolution of the normalized Ag and Ti LEIS signals is plotted versus Ag coverage in Figure 3 and compared with two typical growth models. The Ag coverages reported in this paper are given in monolayer (ML), where 1 ML is defined as 7.36 × 10 18 atoms/m 2 , which is the areal number density of coordinatively unsaturated O atoms on the ideal bulk-terminated TiO 2 (100) surface.…”
Section: Resultsmentioning
confidence: 99%
“…The solid curved lines correspond to the best fit of these data to a 3D growth model called the hemispherical cap model. 73 It assumes that Ag grows as 3D particles with the shape of hemispherical caps and that the Ag particle number density n is saturated by the first dose after which the Ag particles only grow in size and that the Ag particles all have the same shape and same size at any given coverage. Although no study of Ag nanoparticles on TiO 2 (100) has been reported before, STM studies of Ag nanoparticles grown on rutile TiO 2 (110) show that the majority of the islands have nucleated by 0.05 ML (i.e., the saturation density of islands is nearly reached already by ∼0.05 ML) 68 as is generally the case for such systems consisting of late transition metal nanoparticles supported on oxide surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data are well fit using the hemispherical cap model described by Diebold et al, 25 but modified to better describe macroscopic shadowing of the incident ion beam by hemispherical particles. 26 It assumes that the film grows as 3D particles with the shape of 111), respectively) as a function of Cu coverage after deposition onto CeO 1.95 (111) (diamonds) and CeO 1.8 (111) (triangles) at 300 K. The dashed line corresponds to the normalized ISS signal that would be observed if Cu grew in a layer-by-layer fashion, while the solid line corresponds to Cu growing as hemispherical caps with a fixed radius and a fixed particle density of 7.8 × 10 12 particles/ cm 2 . This model is only reasonable up to ∼35% of the surface being covered by particles, since they may start to overlap with each other at higher coverage, so the dotted lines after that are only a guide to the eye.…”
Section: Resultsmentioning
confidence: 99%